2010
DOI: 10.1016/s1734-1140(10)70374-1
|View full text |Cite
|
Sign up to set email alerts
|

Calcium mobilization by the plant estrogen ferutinin does not induce blood platelet aggregation

Abstract: Platelet activation is closely associated with an increase in intracellular Ca(2+) concentration. Various compounds including Ca(2+) ionophores are able to trigger platelet aggregation by increasing intracellular Ca(2+) concentration in platelets. In the present study, we monitored the effect of the phytoestrogen ferutinin, which acts as a Ca(2+) ionophore in human blood platelets; its ionophore-like properties include upregulation of [Ca(2+)](in), activation of fibrinogen receptors and increased fibrinogen bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In agreement with this, earlier studies have demonstrated enhanced [Ca 2+ i ] mobilisation by tamoxifen in platelets stimulated with thrombin (30), Chinese hamster ovary cells (60) and cancer cell lines (61). Although inhibitory action of tamoxifen on platelet aggregation contradicts rise in [Ca 2+ i ], similar observation has also been documented with plant estrogen feruti-nin, which mobilised intracellular calcium in platelets without inducing platelet aggregation (62). Contrarily, a recent report by Chang et al (18) observed suppression of platelet cytosolic Ca 2+ by tamoxifen, which could be attributed to collagen, a different agonist, used by these authors.…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with this, earlier studies have demonstrated enhanced [Ca 2+ i ] mobilisation by tamoxifen in platelets stimulated with thrombin (30), Chinese hamster ovary cells (60) and cancer cell lines (61). Although inhibitory action of tamoxifen on platelet aggregation contradicts rise in [Ca 2+ i ], similar observation has also been documented with plant estrogen feruti-nin, which mobilised intracellular calcium in platelets without inducing platelet aggregation (62). Contrarily, a recent report by Chang et al (18) observed suppression of platelet cytosolic Ca 2+ by tamoxifen, which could be attributed to collagen, a different agonist, used by these authors.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, ferutinin acts as an electrogenic Ca 2+ -ionophore that has been shown to use planar lipid bilayers membranes and liposomes (Zamaraeva et al 1997;Abramov et al 2001;Dubis et al 2015). Similarly, earlier works showed that ferutinin at concentrations of 1-50 µM considerably increased Ca 2+ -permeability of thymocytes, platelets, Jurkat T-cell, erythrocytes, mitochondria, and sarcoplasmic reticulum (Zamaraeva et al 1997(Zamaraeva et al , 1999(Zamaraeva et al , 2010Macho et al 2004;Gao et al 2013). Ferutinin interacts strongly with Ca 2+ -ions via the hydroxyl group of ferutinol and the carboxyl oxygen of the complex ether bond (Dubis et al 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Ferutinin was isolated from the roots of Ferula tenuisecta by the method of Saidkhodjaev and Nikonov (Saidkhodjaev and Nikonov 1973). According to the GC-MS analysis, the purity of ferutinin was 96 ± 2% (Zamaraeva et al 2010). We used ferutinin as 1 mM stock solution in DMSO.…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several species of Ferula genus has been used in folk medicine in digestive disorders, rheumatism, headache, arthritis and as, antispasmodic and aphrodisiac [8]. Ferutinin (Jaeschkeanadiol p-hydroxy benzoate) ( Figure 1A) is mainly found in Ferula hermonis L. "Zallouh", and other Ferula species (like, Ferula tenuisecta) [9]. It belongs to a broad group of sesquiterpene ducane esters [10] and has a wide range of biological activities.…”
Section: Introductionmentioning
confidence: 99%